2022
DOI: 10.3390/v14102180
|View full text |Cite
|
Sign up to set email alerts
|

Pin-Pointing the Key Hubs in the IFN-γ Pathway Responding to SARS-CoV-2 Infection

Abstract: Interferon gamma (IFN-γ) may be potential adjuvant immunotherapy for COVID-19 patients. In this work, we assessed gene expression profiles associated with the IFN-γ pathway in response to SARS-CoV-2 infection. Employing a case-control study from SARS-CoV-2-positive and -negative patients, we identified IFN-γ-associated pathways to be enriched in positive patients. Bioinformatics analyses showed upregulation of MAP2K6, CBL, RUNX3, STAT1, and JAK2 in COVID-19-positive vs. -negative patients. A positive correlati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…IFN-γ is a crucial marker of an induced anti-viral T-cell immune response [13] and plays a central role in fighting SARS-CoV-2 infection [14]. Previously, we have shown that the PHH-1V booster confers an IFN-γ response comparable to BNT162b2 up to day 98 (3 months) [12].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ is a crucial marker of an induced anti-viral T-cell immune response [13] and plays a central role in fighting SARS-CoV-2 infection [14]. Previously, we have shown that the PHH-1V booster confers an IFN-γ response comparable to BNT162b2 up to day 98 (3 months) [12].…”
Section: Discussionmentioning
confidence: 99%
“…The top proteomic contributors in our discriminatory model included interferon-induced GTP-binding protein Mx1 (MX1 or MXA), interferon-stimulated gene 15 (ISG15), Z-DNA-binding protein 1 (ZBP1), and interferon lambda 1 (IFNL1), also referred to as IL-29. Given their responsiveness to IFN signaling, ISG15 and its downstream targets, including MX1 156 , have been implicated as key participants during SARS-CoV-2 infection by using in vitro and in vivo models [157][158][159] as well as samples from COVID-19 patients [160][161][162] . Similarly, the induction of IFNL1 by SARS-CoV-2 infection was previously reported in vitro 163 .…”
Section: Discussionmentioning
confidence: 99%
“…Solving S4 classifiers (4), we get Table 8 as follows. We note that PARP9 was linked to SARS-CoV-1 and MERS-CoV in the literature [18][19][20]35,36]. It has also been extensively studied its connection to SARS-CoV-2 [37][38][39][40].…”
Section: Beta Values Calculated Using (M +1)/(m+u+2)mentioning
confidence: 91%